Modeling Absolute Deviations Method by using Numerical Methods to measure the dispersion of the proposal for error - مرعي, احمد ادريس; طاهر, محمود محمد; طاهر, محمود محمد (Journal of Economics and Administrative Sciences, 2014)
Is in this research review of the way minimum absolute deviations values ​​based on linear programming method to estimate the parameters of simple linear regression model and give an overview of this model. We were modeling method deviations of the absolute values ​​proposed using a scale of dispersion and composition of a simple linear regression model based on the proposed measure. Object of the work is to find the capabilities of not affected by abnormal values by using numerical method and at the lowest possible recurrence.